Preparation method of high-purity CBN micro powder

By adopting the steps of reaction of dehydrated borax and urea, dilute acid soaking, deionized water washing, ball milling and high temperature and high pressure treatment in the production of CBN micro powder, the problems of high impurity content and low strength of CBN micro powder in the existing technology were successfully solved, and the problem was achieved. Preparation of CBN micropowder with high purity, wear resistance and thermal stability.

CN119330369AActive Publication Date: 2025-01-21ZHENGZHOU WODE SUPERHARD MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411519497.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The prior art has problems such as high impurity content, low strength, low conversion rate and large particle size when producing high-purity CBN single crystal fine powder, which is difficult to meet the needs of industrial mass production.

Method used

After dehydrated borax and urea, heated reactions in ammonia gas to generate boron nitride, and after many rare acid soaking, ion water washing, ball grinding and high -temperature and high pressure treatment, the removal of impurities was finally removed by alkali and acid treatment to obtain a high -purity CBN CBN Micro powder.

Benefits of technology

It achieves the preparation of CBN micropowder with high purity (95% ~ 98%), high wear resistance and high thermal stability, improves the conversion rate and particle size fineness, simplifies the production process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330369A_ABST
    Figure CN119330369A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of high-purity CBN (cubic boron nitride) micro powder, which comprises the following steps: mixing dehydrated borax with urea, heating and reacting in ammonia gas flow, and purifying the reaction product to obtain boron nitride; mixing a catalyst, an HBN material and a catalytic additive; the preparation method comprises the following steps: sealing, carrying out static pressure, granulating, pressing to obtain a synthetic column, filling the synthetic column into a pyrophyllite block mechanism to form a synthetic block, filling the synthetic block into a cubic press, knocking and crushing a high-pressure synthetic block sample obtained by high-temperature and high-pressure synthesis, putting into a ball-milling tank, carrying out ball milling, opening the ball-milling tank, adding deionized water, boiling with water, and carrying out vacuum drying to obtain a finished product. Collecting the CBN at the bottom of the container, putting the CBN into a strong alkali solution, boiling, and washing with deionized water; cBN at the bottom of the container is collected and then put into a strong acid solution to be boiled, then deionized water is used for flushing, drying, shaping, screening and shape selecting treatment are conducted, and CBN crystal micro powder is obtained; the invention has the advantages of high purity, good thermal stability, high grinding efficiency, high purity, high wear resistance and high thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of CBN, and in particular relates to a method for preparing high-purity CBN micropowder. Background Art

[0002] Cubic boron nitride and its products are widely used in automobile, machinery, electronics, aviation, aerospace, optical instruments, glass, ceramics, petroleum, geology and other departments. With the continuous development of technology and products, the application of diamond powder and its products in emerging fields such as 3C field, Sic semiconductor processing, photovoltaic and so on has also been fully developed. In the prior art, the industrial production of CBN single crystal powder is mainly to synthesize CBN single crystal abrasive grains first, and then to crush and shape them, and to produce them by a special process method. The CBN single crystal abrasive grains synthesized by the prior method use active precious metals as catalyst materials, and the preservation and synthesis of nitrides are difficult, the cost is high, the process flow is relatively complicated, and the impurity content of the produced products is high and the strength is low. The conversion rate of the prior method is low at 30-40%, and the crystal particle size is large, with a particle size of about 100 mesh, which is not suitable for industrial batch production of single crystal powder. Therefore, it is very necessary to provide a method for preparing high-purity CBN powder with high purity, good thermal stability, high grinding efficiency, high purity, high wear resistance and high thermal stability. Summary of the invention

[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a method for preparing high-purity CBN micropowder with high purity, high wear resistance and high thermal stability.

[0004] The object of the present invention is achieved in this way: a method for preparing high-purity CBN micropowder, the method comprising the following steps:

[0005] Step 1: Mix dehydrated borax and urea, heat and react in an ammonia stream, and purify the product obtained by the reaction to obtain boron nitride;

[0006] Step 2: Mix 200 mesh anhydrous borax and urea in a molar ratio of 1:2.3-2.5 to generate an intermediate of borax and urea;

[0007] Step 3: After cooling the intermediate, crush it into 300-350 mesh, press it into blocks with a mold on a press, and then send it into a nitriding furnace to react in an ammonia flow for about 6-8 hours; then stop heating, introduce ammonia, stop introducing ammonia when the furnace temperature cools to below 300-400°C, and continue cooling to an appropriate temperature;

[0008] Step 4: Take out the crude boron nitride, crush it to 200 mesh, soak it in dilute acid twice, each time for about 12 to 15 hours, then wash it with deionized water several times until it is neutral, filter, dry and crush it to obtain a boron nitride product with a purity of 95% to 98%;

[0009] Step 5: According to the weight ratio, 2-15 parts of catalyst, 80-93 parts of HBN material and 0.2-4.5 parts of catalytic additive are mixed in a three-dimensional mixer for 10 hours;

[0010] Step 6: After sealing the mixed materials in the previous step, static pressing and granulation are performed to press them into synthetic columns of a certain size, and the synthetic columns are placed in a vacuum reduction furnace for reduction using a step-by-step reduction process. The reduction temperature range is 1150-1200°C, and the reduction time is not less than 6 hours. The reduced synthetic columns are vacuum packaged for standby use;

[0011] Step 7: Load the synthetic column formed in the previous step into the pyrophyllite block mechanism to form a synthetic block, and then load the synthetic block into the high-pressure chamber of the six-sided top press, pressurize it to 3-7GPa, heat it to 1200-1400℃, and last for 4-8h until a high-pressure synthetic block sample is obtained;

[0012] Step 8: The high-pressure synthesis block sample obtained by high-temperature and high-pressure synthesis is crushed by tapping, and then the crushed material is placed in a ball mill, and a certain amount of ball milling medium and dry ball milling reagent are added, and the lid is closed;

[0013] Step 9: Place the ball mill in the ball mill, adjust the speed to 400 rpm, rotate for 10 hours, and rotate alternately;

[0014] Step 10: After the ball mill stops working, open the ball mill jar. The mixture in the ball mill jar is agglomerated and attached to the wall of the jar. Add a certain amount of deionized water to wet the mixture in the ball mill jar. The mixture is softened and dispersed in the deionized water. The pH value is about 8 when measured with a pH test paper. After the mixed liquid is ultrasonicated in a water bath for 2 hours, the liquid mixture is transferred to a dialysis belt for dialysis to remove urea. After dialysis in a water bath at 35°C for a period of time, the mixture is centrifuged at 3000 rpm for 30 minutes.

[0015] Step 11: Due to the high density of CBN single crystal, the precipitate is deposited at the bottom of the container, the solution in the container is filtered out, and it is boiled with deionized water, and repeated 4-6 times to remove most of the cubic boron nitride powder;

[0016] Step 12: Then collect the CBN at the bottom of the container and put it into a strong alkaline solution and boil it for 20-30 minutes, then rinse it with deionized water to remove the residual cubic boron nitride powder; then collect the CBN at the bottom of the container and put it into a strong acid solution and boil it for 20-30 minutes, then rinse it repeatedly with deionized water to remove the residual metal impurities;

[0017] Step 13: Then put the obtained CBN into an oven at 110-140°C for drying for 8 hours, and shape the pure CBN. After shaping, it needs to be screened and selected to obtain CBN crystal powder.

[0018] The reaction formula of step 1 is: Na 2 B 4 O7+2(NH 2 ) 2 CO→4BN+Na 2 O+4H 2 O+2CO 2 .

[0019] The specific steps of step 2 are as follows: 200-mesh anhydrous borax and urea are mixed in a molar ratio of 1:2.3-2.5; since urea contains a small amount of free water, it is very easy to form a mass and is not easy to mix evenly; therefore, it is necessary to dry it at 100° C. before mixing, crush it to 200 mesh, and then mix it with 200-mesh anhydrous borax; the mixed material is placed in a reactor at a temperature of 200-400° C. for condensation reaction for about 3-5 hours to generate an intermediate of borax and urea.

[0020] The temperature condition for the reaction in the ammonia gas flow in step 3 is: 800-1050°C or 1000-1200°C.

[0021] The catalyst in step 5 is one of alkali metal, alkaline earth metal and its nitride catalyst, aluminum-based alloy catalyst and water catalyst.

[0022] The alkali metal, alkaline earth metal and its nitride catalyst adopts Ca 3 B 2 N 4 ; The aluminum-based alloy catalyst is one of Al-Si, Al-Ni, Al-Cr, Al-Mn, and Al-Co.

[0023] The catalytic additive in step 5 is Al, La, B 4 C, and the purity of each of them is above 99.99%.

[0024] The ball milling medium in step 8 is zirconium oxide balls, and the dry ball milling reagent is urea.

[0025] The ball mill in step 9 is a planetary ball mill for mechanical ball milling.

[0026] The alkali treatment of cubic boron nitride and pyrophyllite in step 12 is specifically as follows: low-temperature molten K and Na metal hydroxides can dissolve cubic boron nitride and have no effect on CBN; to prevent corrosion of CBN at high temperatures, a mixed alkali of NaOH:KOH=1:2 mass ratio can be used to lower the melting point; after the alkali treatment, the dissolved matter is washed away with deionized water, and the solution is acid washed to neutrality to obtain CBN.

[0027] Beneficial effects of the present invention: The present invention is a method for preparing high-purity CBN micropowder. During use, the catalyst of the present invention adopts high-quality catalyst, meets kinetic conditions, and meets stable thermodynamic conditions, i.e., stable PT conditions, at a stable high temperature. The catalyst in a molten state dissolves HBN, and then precipitates CBN crystals, and the crystal nuclei gradually grow under appropriate high temperature and high pressure conditions. The purification process of the method of the present invention can effectively remove most of the cubic boron nitride powder; and remove the residual cubic boron nitride powder by alkali treatment, and then remove the residual metal impurities by acid treatment, so as to obtain a purer cubic boron nitride micropowder. The boron nitride product with a purity of 95% to 98% is obtained; the CBN prepared by the method of the invention is all black cubic boron nitride micropowder, which is commonly used in resin binder systems, grinding oilstones, etc.; the preparation method of the invention has high CBN conversion rate, fine particle size, and a yield of about 45%, simplifies the production process of CBN single crystal micropowder, reduces the synthesis cost and synthesis pressure conditions, and has good economic and social benefits; the CBN micropowder product prepared by the method of the invention has high purity, high wear resistance, and high thermal stability, and is used for the production of PCBN composite sheets and polycrystalline sintered bodies with longer service life; the invention has the advantages of high purity, high wear resistance, and high thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of SED of the present invention Figure 1 .

[0029] Figure 2 Schematic diagram of SED of the present invention Figure 2 .

[0030] Figure 3 Schematic diagram of SED of the present invention Figure 3 .

[0031] Figure 4 Schematic diagram of SED of the present invention Figure 4 . DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] Example 1

[0034] like Figure 1-4 As shown, a method for preparing high-purity CBN micropowder comprises the following steps:

[0035] Step 1: Mix dehydrated borax and urea, heat and react in an ammonia stream, and purify the product obtained by the reaction to obtain boron nitride;

[0036] Step 2: Mix 200 mesh anhydrous borax and urea in a molar ratio of 1:2.3 to generate an intermediate of borax and urea;

[0037] Step 3: After cooling, the intermediate is crushed to 300 mesh, pressed into blocks with a mold on a press, and then sent to a nitriding furnace to react in an ammonia flow for about 6 hours; then stop heating, introduce ammonia, stop introducing ammonia when the furnace temperature cools to below 300°C, and continue cooling to an appropriate temperature;

[0038] Step 4: Take out the crude boron nitride, crush it to 200 mesh, soak it in dilute acid twice, each time for about 12 hours, then wash it with deionized water several times until it is neutral, filter, dry and crush it to obtain a boron nitride product with a purity of 95%;

[0039] Step 5: According to the weight ratio, 2 parts of catalyst, 80 parts of HBN material and 0.2 parts of catalytic additive are mixed in a three-dimensional mixer for 10 hours;

[0040] Step 6: After sealing the mixed materials in the previous step, static pressing and granulation are performed to press them into synthetic columns of a certain size, and the synthetic columns are placed in a vacuum reduction furnace for reduction using a step-by-step reduction process. The reduction temperature range is 1150°C, and the reduction time is not less than 6 hours. The reduced synthetic columns are vacuum packaged for standby use;

[0041] Step 7: Place the synthetic column formed in the previous step into the pyrophyllite block mechanism to form a synthetic block, then place the synthetic block into the high-pressure chamber of the six-sided top press, pressurize it to 3 GPa, heat it to 1200 ° C, and hold it for 4 hours until a high-pressure synthetic block sample is obtained;

[0042] Step 8: The high-pressure synthesis block sample obtained by high-temperature and high-pressure synthesis is crushed by tapping, and then the crushed material is placed in a ball mill, and a certain amount of ball milling medium and dry ball milling reagent are added, and the lid is closed;

[0043] Step 9: Place the ball mill in the ball mill, adjust the speed to 400 rpm, rotate for 10 hours, and rotate alternately;

[0044] Step 10: After the ball mill stops working, open the ball mill jar. The mixture in the ball mill jar is agglomerated and attached to the wall of the jar. Add a certain amount of deionized water to wet the mixture in the ball mill jar. The mixture is softened and dispersed in the deionized water. The pH value is about 8 when measured with a pH test paper. After the mixed liquid is ultrasonicated in a water bath for 2 hours, the liquid mixture is transferred to a dialysis belt for dialysis to remove urea. After dialysis in a water bath at 35°C for a period of time, the mixture is centrifuged at 3000 rpm for 30 minutes.

[0045] Step 11: Due to the high density of CBN single crystal, the precipitate is deposited at the bottom of the container, the solution in the container is filtered out, and it is boiled with deionized water. This is repeated 4 times to remove most of the cubic boron nitride powder;

[0046] Step 12: Then collect the CBN at the bottom of the container and put it into a strong alkaline solution and boil it for 20 minutes, then rinse it with deionized water to remove the residual cubic boron nitride powder; then collect the CBN at the bottom of the container and put it into a strong acid solution and boil it for 20 minutes, then rinse it repeatedly with deionized water to remove the residual metal impurities;

[0047] Step 13: The obtained CBN is then placed in an oven at 110°C for drying for 8 hours, and the pure CBN is shaped. After shaping, screening and selection treatment are performed to obtain CBN crystal powder.

[0048] In this embodiment, in order to further illustrate the performance of the present invention, specific effect data are provided below; the impurity content is determined by ICP method and nitrogen and oxygen analysis method, and the specific surface area and particle size composition of the sample are determined by specific surface area measuring instrument and laser particle size analyzer. The component composition and physical properties of HBN prepared by the preparation method of the present invention are shown in Table 1 and Table 2;

[0049] Table 1 Components of HBN prepared by borax and urea method

[0050]

[0051] Table 2 Physical properties of HBN prepared by borax and urea method

[0052]

[0053] The present invention is a method for preparing high-purity CBN micropowder. In use, the catalyst of the present invention adopts high-quality catalyst, meets the kinetic conditions, meets the stable thermodynamic conditions, i.e., the stable PT conditions, at a stable high temperature, the catalyst in a molten state dissolves HBN, and then precipitates CBN crystals, and the crystal nuclei gradually grow under appropriate high temperature and high pressure conditions; the purification process of the method of the present invention can effectively remove most of the cubic boron nitride powder; and remove the residual cubic boron nitride powder by alkali treatment, and then remove the residual metal impurities by acid treatment, so as to obtain a purer cubic boron nitride micropowder, i.e., a purity of 9 5% to 98% of boron nitride products; the CBN prepared by the method of the invention is all black cubic boron nitride micropowder, which is commonly used in resin binder systems, grinding stones, etc.; the preparation method of the invention has high CBN conversion rate, fine particle size, and a yield of about 45%, simplifies the production process of CBN single crystal micropowder, reduces synthesis cost and synthesis pressure conditions, and has good economic and social benefits; the CBN micropowder product prepared by the method of the invention has high purity, high wear resistance, and high thermal stability, and is used for the preparation of longer-life PCBN composite sheets and polycrystalline sintered bodies; the invention has the advantages of high purity, high wear resistance, and high thermal stability.

[0054] Example 2

[0055] like Figure 1-4 As shown, a method for preparing high-purity CBN micropowder comprises the following steps:

[0056] Step 1: Mix dehydrated borax and urea, heat and react in an ammonia stream, and purify the product obtained by the reaction to obtain boron nitride;

[0057] Step 2: Mix 200 mesh anhydrous borax and urea in a molar ratio of 1:2.4 to generate an intermediate of borax and urea;

[0058] Step 3: After cooling, the intermediate is crushed to 325 mesh, pressed into blocks with a mold on a press, and then sent to a nitriding furnace to react in an ammonia flow for about 7 hours; then stop heating, introduce ammonia, stop introducing ammonia when the furnace temperature cools to below 350°C, and continue cooling to an appropriate temperature;

[0059] Step 4: Take out the crude boron nitride, crush it to 200 mesh, soak it in dilute acid twice, each time for about 13 hours, then wash it with deionized water several times until it is neutral, filter, dry and crush it to obtain a boron nitride product with a purity of 96.5%;

[0060] Step 5: According to the weight ratio, 8.5 parts of catalyst, 8.65 parts of HBN material and 2.3 parts of catalytic additive were mixed in a three-dimensional mixer for 10 hours;

[0061] Step 6: After sealing the mixed materials in the previous step, static pressing and granulation are performed to press them into synthetic columns of a certain size, and the synthetic columns are placed in a vacuum reduction furnace for reduction using a step-by-step reduction process. The reduction temperature range is 1175°C, and the reduction time is not less than 6 hours. The reduced synthetic columns are vacuum packaged for standby use;

[0062] Step 7: Load the synthetic column formed in the previous step into the pyrophyllite block mechanism to form a synthetic block, and then load the synthetic block into the high-pressure chamber of the six-sided top press, pressurize it to 5GPa, heat it to 1300℃, and last for 6 hours until a high-pressure synthetic block sample is obtained;

[0063] Step 8: The high-pressure synthesis block sample obtained by high-temperature and high-pressure synthesis is crushed by tapping, and then the crushed material is placed in a ball mill, and a certain amount of ball milling medium and dry ball milling reagent are added, and the lid is closed;

[0064] Step 9: Place the ball mill in the ball mill, adjust the speed to 400 rpm, rotate for 10 hours, and rotate alternately;

[0065] Step 10: After the ball mill stops working, open the ball mill jar. The mixture in the ball mill jar is agglomerated and attached to the wall of the jar. Add a certain amount of deionized water to wet the mixture in the ball mill jar. The mixture is softened and dispersed in the deionized water. The pH value is about 8 when measured with a pH test paper. After the mixed liquid is ultrasonicated in a water bath for 2 hours, the liquid mixture is transferred to a dialysis belt for dialysis to remove urea. After dialysis in a water bath at 35°C for a period of time, the mixture is centrifuged at 3000 rpm for 30 minutes.

[0066] Step 11: Due to the high density of CBN single crystal, the precipitate is deposited at the bottom of the container, the solution in the container is filtered out, and it is boiled with deionized water. This is repeated 5 times to remove most of the cubic boron nitride powder;

[0067] Step 12: Then collect the CBN at the bottom of the container and put it into a strong alkaline solution and boil it for 25 minutes, then rinse it with deionized water to remove the residual cubic boron nitride powder; then collect the CBN at the bottom of the container and put it into a strong acid solution and boil it for 25 minutes, then rinse it repeatedly with deionized water to remove the residual metal impurities;

[0068] Step 13: The obtained CBN is then placed in an oven at 125°C for drying for 8 hours, and the pure CBN is shaped. After shaping, screening and selection treatment are performed to obtain CBN crystal powder.

[0069] The present invention is a method for preparing high-purity CBN micropowder. In use, the catalyst of the present invention adopts high-quality catalyst, meets the kinetic conditions, meets the stable thermodynamic conditions, i.e., the stable PT conditions, at a stable high temperature, the catalyst in a molten state dissolves HBN, and then precipitates CBN crystals, and the crystal nuclei gradually grow under appropriate high temperature and high pressure conditions; the purification process of the method of the present invention can effectively remove most of the cubic boron nitride powder; and remove the residual cubic boron nitride powder by alkali treatment, and then remove the residual metal impurities by acid treatment, so as to obtain a purer cubic boron nitride micropowder, i.e., a purity of 9 5% to 98% of boron nitride products; the CBN prepared by the method of the invention is all black cubic boron nitride micropowder, which is commonly used in resin binder systems, grinding stones, etc.; the preparation method of the invention has high CBN conversion rate, fine particle size, and a yield of about 45%, simplifies the production process of CBN single crystal micropowder, reduces synthesis cost and synthesis pressure conditions, and has good economic and social benefits; the CBN micropowder product prepared by the method of the invention has high purity, high wear resistance, and high thermal stability, and is used for the preparation of longer-life PCBN composite sheets and polycrystalline sintered bodies; the invention has the advantages of high purity, high wear resistance, and high thermal stability.

[0070] Example 3

[0071] like Figure 1-4 As shown, a method for preparing high-purity CBN micropowder comprises the following steps:

[0072] Step 1: Mix dehydrated borax and urea, heat and react in an ammonia stream, and purify the product obtained by the reaction to obtain boron nitride;

[0073] Step 2: Mix 200 mesh anhydrous borax and urea in a molar ratio of 1:2.5 to generate an intermediate of borax and urea;

[0074] Step 3: After cooling, the intermediate is crushed to 350 mesh, pressed into blocks with a mold on a press, and then sent to a nitriding furnace to react in an ammonia flow for about 8 hours; then stop heating, introduce ammonia, stop introducing ammonia when the furnace temperature cools to below 400°C, and continue cooling to an appropriate temperature;

[0075] Step 4: Take out the crude boron nitride, crush it to 200 mesh, soak it in dilute acid twice, each time for about 15 hours, then wash it with deionized water several times until it is neutral, filter, dry and crush it to obtain a boron nitride product with a purity of 98%;

[0076] Step 5: According to the weight ratio, 15 parts of catalyst, 93 parts of HBN material and 4.5 parts of catalytic additive were mixed in a three-dimensional mixer for 10 hours;

[0077] Step 6: After sealing the mixed materials in the previous step, static pressing and granulation are performed to press them into synthetic columns of a certain size, and the synthetic columns are placed in a vacuum reduction furnace for reduction using a step-by-step reduction process. The reduction temperature range is 1200°C, and the reduction time is not less than 6 hours. The reduced synthetic columns are vacuum packaged for standby use;

[0078] Step 7: Load the synthetic column formed in the previous step into the pyrophyllite block mechanism to form a synthetic block, and then load the synthetic block into the high-pressure chamber of the six-sided top press, pressurize it to 7GPa, heat it to 1400℃, and last for 8h until a high-pressure synthetic block sample is obtained;

[0079] Step 8: The high-pressure synthesis block sample obtained by high-temperature and high-pressure synthesis is crushed by tapping, and then the crushed material is placed in a ball mill, and a certain amount of ball milling medium and dry ball milling reagent are added, and the lid is closed;

[0080] Step 9: Place the ball mill in the ball mill, adjust the speed to 400 rpm, rotate for 10 hours, and rotate alternately;

[0081] Step 10: After the ball mill stops working, open the ball mill jar. The mixture in the ball mill jar is agglomerated and attached to the wall of the jar. Add a certain amount of deionized water to wet the mixture in the ball mill jar. The mixture is softened and dispersed in the deionized water. The pH value is about 8 when measured with a pH test paper. After the mixed liquid is ultrasonicated in a water bath for 2 hours, the liquid mixture is transferred to a dialysis belt for dialysis to remove urea. After dialysis in a water bath at 35°C for a period of time, the mixture is centrifuged at 3000 rpm for 30 minutes.

[0082] Step 11: Due to the high density of CBN single crystal, the precipitate is deposited at the bottom of the container, the solution in the container is filtered out, and it is boiled with deionized water, and repeated 6 times to remove most of the cubic boron nitride powder;

[0083] Step 12: Then collect the CBN at the bottom of the container and put it into a strong alkaline solution and boil it for 30 minutes, then rinse it with deionized water to remove the residual cubic boron nitride powder; then collect the CBN at the bottom of the container and put it into a strong acid solution and boil it for 30 minutes, then rinse it repeatedly with deionized water to remove the residual metal impurities;

[0084] Step 13: The obtained CBN is then placed in an oven at 140°C for drying for 8 hours, and the pure CBN is shaped. After shaping, screening and selection treatment are performed to obtain CBN crystal powder.

[0085] In this example, in order to further illustrate the performance of the present invention, specific effect data are provided below; in order to further quantify the characteristics of CBN powder, CBN powder was selected and its structure was carefully characterized using a scanning electron microscope. The results are as follows: Figure 1-4As shown; Magnetic susceptibility: The magnetic susceptibility was measured by using a JCC-B magnetic susceptibility tester, and 6 batches of ordinary CBN micropowder and 6 batches of the CBN micropowder of the present invention were selected, and the average magnetic susceptibility was calculated, as shown in Table 3;

[0086] Comparison of CBN magnetic susceptibility in Table 32

[0087]

[0088]

[0089] From the magnetic susceptibility measurement results in Table 3, it can be seen that the average magnetic susceptibility of the CBN of the present invention is reduced by 1.8×10 -5 SI, the decrease is more than 65%, which is much lower than that of ordinary CBN; the magnetic susceptibility of CBN is caused by its internal metal impurities, and the more such impurities are, the stronger the magnetism of CBN; this shows that the internal impurities of the CBN of the present invention are far less than those of ordinary CBN; the CBN prepared by the preparation method of the present invention is black cubic boron nitride powder, which has high crystal purity, good thermal stability, good self-sharpening, high grinding efficiency and the like.

[0090] The present invention is a method for preparing high-purity CBN micropowder. In use, the catalyst of the present invention adopts high-quality catalyst, meets the kinetic conditions, meets the stable thermodynamic conditions, i.e., the stable PT conditions, at a stable high temperature, the catalyst in a molten state dissolves HBN, and then precipitates CBN crystals, and the crystal nuclei gradually grow under appropriate high temperature and high pressure conditions; the purification process of the method of the present invention can effectively remove most of the cubic boron nitride powder; and remove the residual cubic boron nitride powder by alkali treatment, and then remove the residual metal impurities by acid treatment, so as to obtain a purer cubic boron nitride micropowder, i.e., a purity of 9 5% to 98% of boron nitride products; the CBN prepared by the method of the invention is all black cubic boron nitride micropowder, which is commonly used in resin binder systems, grinding stones, etc.; the preparation method of the invention has high CBN conversion rate, fine particle size, and a yield of about 45%, simplifies the production process of CBN single crystal micropowder, reduces synthesis cost and synthesis pressure conditions, and has good economic and social benefits; the CBN micropowder product prepared by the method of the invention has high purity, high wear resistance, and high thermal stability, and is used for the preparation of longer-life PCBN composite sheets and polycrystalline sintered bodies; the invention has the advantages of high purity, high wear resistance, and high thermal stability.

Claims

1. A method for preparing high-purity CBN micropowder, characterized in that: The method comprises the following steps: Step 1: Mix 200 mesh anhydrous borax and dried urea in a molar ratio of 1: 2.3-2.5, and the mixed materials undergo condensation reaction for about 2-4 hours to generate an intermediate of borax and urea; Step 2: The intermediate is cooled to 60°C and then crushed, and then the 80-mesh sieve is placed in a nitriding furnace and flows in a nitriding liquid at 800-950°C for about 2-4 hours. The product after the reaction is cooled in an ammonia atmosphere and then pickled, washed and dried to obtain a fast boron nitride BN product; Step 3: 2-15 parts of catalyst, 80-93 parts of B4C, 56-65 parts of BN powder and 0.2-4.5 parts of catalytic additive are mixed in a three-dimensional mixer for 10 hours; Step 4: Place the mixed powder prepared in the previous step into a high temperature furnace and heat it at high temperature; Step 5: Place the mixed powder material formed in the previous step in a reactor, introduce nitrogen- and boron-containing gases, and carry out chemical reactions at a certain temperature and pressure, so that B4C and BN react to form CBN micropowders; control the time and temperature of the heat treatment to obtain the desired CBN micropowder size and shape; Step 6: After cooling, the prepared CBN powder was placed in a ball mill, the ball mill was placed in a ball mill, the speed was adjusted to 400 rpm, the rotation time was 10 hours, and the rotation was performed alternately; Step 7: After the ball mill stops working, open the ball mill jar, add a certain amount of deionized water to wet the mixture in the ball mill jar, soften the mixture and disperse it in deionized water, ultrasonicate the mixed liquid in a water bath for 2 hours, transfer the liquid mixture to a dialysis belt to dialyze to remove urea, dialyze in a water bath at 35°C for a period of time, and centrifuge at 3000rpm for 30 minutes; Step 8: Due to the high density of CBN single crystal, the precipitate is deposited at the bottom of the container, the solution in the container is filtered out, and it is boiled with deionized water. This is repeated 4-6 times to remove most of the cubic boron nitride powder. Step 9: The obtained CBN is then placed in an oven at 110-140°C for drying for 8 hours, and the dried powder is sieved, sieved and finely processed to remove impurities and particles that do not meet the requirements, thereby obtaining CBN crystal micropowder.

2. The method for preparing high-purity CBN micropowder according to claim 1, characterized in that: The reaction formula in step 1 is: Na2B4O7+2(NH2)2CO→4BN+Na2O+4H2O+2CO2.

3. The method for preparing high-purity CBN micropowder according to claim 1, characterized in that: The specific steps of step 2 are: taking out the crude boron nitride and crushing it, then soaking it in dilute acid twice, each time for about 12 to 15 hours, then washing it with deionized water several times until it is neutral, filtering, drying and crushing to obtain a boron nitride product with a purity of 95% to 98%.

4. The method for preparing high-purity CBN powder according to claim 1, characterized in that: The B4C powder in step 3 is prepared by a sol-gel method or a co-precipitation method.

5. The method for preparing high-purity CBN powder according to claim 1, characterized in that: The catalyst in step 3 is one of alkali metal, alkaline earth metal and its nitride catalyst, aluminum-based alloy catalyst and water catalyst.

6. The method for preparing high-purity CBN powder according to claim 5, characterized in that: The alkali metal, alkaline earth metal and their nitride catalysts are Ca3B2N4; the aluminum-based alloy catalyst is one of Al-Si, Al-Ni, Al-Cr, Al-Mn and Al-Co.

7. The method for preparing high-purity CBN powder according to claim 1, characterized in that: The catalytic additive in step 3 is one or more of Al, La, and B4C, and the purity of each of them is above 99.99%.

8. The method for preparing high-purity CBN powder according to claim 1, characterized in that: The temperature range in step 4 is 1150-1200° C., and the time is not less than 6 hours.

9. The method for preparing high-purity CBN powder according to claim 1, characterized in that: The chemical reaction temperature and pressure in step 5 are: heating to 1200-1400° C., pressurizing to 3-7 GPa, and lasting for 4-8 hours.

Citation Information

Patent Citations

  • Manufacturing method for cubic boron nitride crystals

    CN104667826A

  • Preparation method for cubic boron nitride

    CN110255512A

  • Preparation method of large-particle CBN (cubic boron nitride)

    CN115044978A

  • Method for preparing biomorphic boron nitride by cotton fiber template method

    CN115974010A

  • Method for ball milling water thermal synthesis of boron nitride

    CN1613751A